1999
DOI: 10.1046/j.1365-2044.1999.00802.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of maternal ambulation on labour with low‐dose combined spinal–epidural analgesia

Abstract: SummaryTwo hundred and twenty-nine nulliparous women who requested regional analgesia during labour were given a combined spinal-epidural block. They were randomly allocated to stay in bed or spend at least 20 min of every hour out of bed. There was no significant difference in duration of labour, analgesia requirements, mode of delivery or condition of the baby between the groups. Ambulation appeared to be safe for the mother and baby. Maternal satisfaction with the low-dose combined spinal-epidural was high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 14 publications
1
34
0
Order By: Relevance
“…Of these, 107 were excluded -40 duplicate citations and 67 did not meet the eligibility criteria. Of five randomized, controlled trials of women with epidural analgesia randomized to upright positions, three were excluded, because the upright position was only during the first stage of labor (8)(9)(10). The features of the two included studies have been summarized in Table I (7,14).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, 107 were excluded -40 duplicate citations and 67 did not meet the eligibility criteria. Of five randomized, controlled trials of women with epidural analgesia randomized to upright positions, three were excluded, because the upright position was only during the first stage of labor (8)(9)(10). The features of the two included studies have been summarized in Table I (7,14).…”
Section: Resultsmentioning
confidence: 99%
“…Although women with epidural analgesia may potentially get the greatest benefit from such management, they are often kept recumbent because of motor block, fetal monitoring, intravenous infusions, and bladder catheterization. However, the current use of low-dose epidurals means that women with epidurals are no longer restricted to bed or if in bed can more easily move about and adopt various positions (7)(8)(9)(10). Further, an observational study among women with low-dose epidural analgesia found that the instrumental delivery rate among women who ambulated from 9-cm dilatation was 32%, compared to 45% for women who chose to remain recumbent (11).…”
mentioning
confidence: 99%
“…A US trial which included randomisation to a mobile CSE with and without active encouragement to ambulate, showed that, although ambulation occurred differentially (66% vs 15%), there was no difference in delivery mode [7]. A UK trial, comparing CSE with and without ambulation, also found no difference in delivery mode between ambulatory and non‐ambulatory groups [8], despite greater differences between groups in ambulation (86% vs 13%).…”
Section: Discussionmentioning
confidence: 99%
“…The “walking epidural”, typically described as a low-concentration local analgesic 35 or opioid-only technique that minimizes motor blockade of the lower extremities, was thought to hold promise for hastening labor by allowing for ambulation. In the three randomized control studies 3537 , there was no effect on labor progression benefit with maternal ambulation during neuraxial analgesia. These studies also concluded that maternal ambulation had no effect on analgesia requirement or mode of delivery.…”
Section: Fallaciesmentioning
confidence: 94%